Biggest,Strongest,Fastest - Jenkins, Steve (New York Ticknor & Fields Books for Young Readers, 1995)
Text and illustrations tell about a variety of animals in wild and their unique abilities
Primary/elementary
Keywords: Jenkins, Steve -- animals-miscellanea- juvenile literature -- animals-miscellanea